Feasibility of a reconfigured domestic violence and abuse training and support intervention responding to affected women, men, children and young people through primary care - Szilassy, E; Coope, C; Emsley, E; Williamson, E; Barbosa, EC; Johnson, M; Dowrick, A; Feder, G (BioMed Central, 2024)
Background: Identification in UK general practice of women affected by domestic violence and abuse (DVA) is increasing, but men and children/young people (CYP) are rarely identified and referred for specialist support. To address this gap, we collaborated with IRISi (UK social enterprise) to strengthen elements of the IRIS + intervention which included the identification of men, direct engagement with CYP, and improved guidance on responding to information received from other agencies. IRIS + was an adaptation of the national IRIS (Identification and Referral to Improve Safety) model focused on the needs of women victim-survivors of DVA. Without diminishing the responses to women, IRIS + also responded to the needs of men experiencing or perpetrating DVA, and CYP living with DVA and/or experiencing it in their own relationships. Our study tested the feasibility of the adapted IRIS + intervention in England and Wales between 2019–21. Methods: We used mixed method analysis to triangulate data from various sources (pre/post intervention questionnaires with primary care clinicians; data extracted from medical records and DVA agencies; semi-structured interviews with clinicians, service providers and referred adults and children) to assess the feasibility and acceptability of the IRIS + intervention. Results: The rate of referral for women doubled (21.6/year/practice) from the rate (9.29/year/practice) in the original IRIS trial. The intervention also enabled identification and direct referral of CYP (15% of total referrals) and men (mostly survivors, 10% of total referrals). Despite an increase in self-reported clinician preparedness to respond to all patient groups, the intervention generated a low number of men perpetrator referrals (2% of all referrals). GPs were the principal patient referrers. Over two-thirds of referred women and CYP and almost half of all referred men were directly supported by the service. Many CYP also received IRIS + support indirectly, via the referred parents. Men and CYP supported by IRIS + reported improved physical and mental health, wellbeing, and confidence. Conclusions: Although the study showed acceptability and feasibility, there remains uncertainty about the effectiveness, cost-effectiveness, and scalability of IRIS + . Building on the success of this feasibility study, the next step should be trialling the effectiveness of IRIS + implementation to inform service implementation decisions.